2020
DOI: 10.1155/2020/3412490
|View full text |Cite
|
Sign up to set email alerts
|

Altered Macular Vasculature in Migraine Patients without Aura: Is It Associated with Ocular Vasculature and White Matter Hyperintensities?

Abstract: Aim. We aimed to determine the alterations in macular and optic nerve vasculature in patients with migraine without aura using optical coherence tomography-angiography (OCTA). We also aimed to determine whether there were clinical differences and alterations in ocular structures in migraine cases with white matter hyperintensities (WMH) using magnetic resonance imaging (MRI). Materials and Methods. The study group comprised patients with migraine without aura and age- and sex-matched healthy controls. Detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…Six studies ( 1 , 17 , 20 , 22 , 23 , 29 ) reported FAZ in patients with MA, three of which ( 1 , 23 , 29 ) showed increased FAZ compared with HC, while the other three ( 17 , 20 , 22 ) reported no significant difference. Among the six studies that reported FAZ in MO patients, only one study ( 28 ) stated that FAZ increased in MO patients compared with HC (MA vs. HC: 0.35 ± 0.11 vs. 0.24 ± 0.12), while the remaining five ( 1 , 17 , 19 , 20 , 23 ) showed no significant difference. FAZ in MA and MO patients was compared in four studies and all of them indicated no statistical difference ( 1 , 17 , 20 , 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies ( 1 , 17 , 20 , 22 , 23 , 29 ) reported FAZ in patients with MA, three of which ( 1 , 23 , 29 ) showed increased FAZ compared with HC, while the other three ( 17 , 20 , 22 ) reported no significant difference. Among the six studies that reported FAZ in MO patients, only one study ( 28 ) stated that FAZ increased in MO patients compared with HC (MA vs. HC: 0.35 ± 0.11 vs. 0.24 ± 0.12), while the remaining five ( 1 , 17 , 19 , 20 , 23 ) showed no significant difference. FAZ in MA and MO patients was compared in four studies and all of them indicated no statistical difference ( 1 , 17 , 20 , 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…The part of data about foveal and parafoveal VD were not included due to the lack of standard deviation in the Bingöl Kiziltunç's study ( 20 ). In the study of Taşli and Ersoy ( 28 ), migraine patients were divided into groups with and without white matter hyperintensities (WMH), and we only included data from the group without WMH. We summarized OCTA devices, parameters, and methods used in included studies in Supplementary Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 150 papers were included [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ,…”
Section: Resultsunclassified